Voice for Voiceless: A cause of concern (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Each and every creature on this planet is gifted with the same means and resources by this world. However, one group claims itself to rule and control the lives of the rest: humans. Other creatures are mercifully exploited by human beings just to satisfy their numerous desires, desire of taste, business, research and many more. They strongly believe that all the creatures in this world are born for the sake of their benefit and they have the right to sacrifice them even for the most frivolous interest of their own. These creatures are poached, maimed, killed and trafficked in vicious ways. Frequently, they are subjected to spiritual rituals and are sacrificed in the name of deity; many times, butchered in horrendous ways for their skins and meats. Tortured, confined and chained, they are coerced into putting up shows for their human counterparts. This paper analyses the acts and policies mentioned under the Constitution of India and discusses the opportunities wherein new rules could be introduced for the protection of fundamental rights for these animals. It also aims to suggest a model that ensures the security and the wellbeing of strays at the local level.